Respon Petani Terhadap Program AUTP (Asuransi Usaha Tani Padi) di Desa Gondangmanis Kecamatan Bandarkedungmulyo Kabupaten Jombang - Mulyanto, Mulyanto; Sidhi, Eko Yuliarsha; Artini, Widi; Reksa Nanda Prayoga; Lisanty, Nina (Universitas Kadiri, 2025)
Agricultural insurance plays an important role in protecting farmers' agricultural businesses. It provides guarantees against risks that may occur in farm businesses. This guarantee is given to farmers who experience losses from crop damage caused by natural factors such as drought, floods, and pest attacks. Insurance is provided through the Rice Farming Business Insurance Program (AUTP). The study aims to determine the response of farmers who cultivate rice plants to AUTP in Gondangmanis Village, Bandarkedungmulyo District, Jombang Regency. In this study, the sample of farmers used as research objects involved 118 sharecroppers who had received the AUTP program as respondents to the AUTP program. The number of respondents was 6 who participated in the AUTP program in the Manisrenggo farmer group, and 6 respondents participated in the AUTP program in the Gondangmanis farmer group. Two data sources are used in this study, namely primary data and secondary data. The research data were analyzed using validity tests and reliability tests. Farmer responses to the implementation of the AUTP program were valued at 69.92. This value has an average index formula of 87.40%, indicating that respondents Strongly Agree (ss) with the objectives, benefits, and implementation of the AUTP program in Gondangmanis Village, Bandarkedungmulyo District, Jombang Regency. Asuransi Pertanian, berperan penting bagi petani dalam melindungi usaha pertanian mereka. Hal memberikan jaminan terhadap risiko yang mungkin terjadi dalam usaha pertanian. Jaminan ini diberikan kepada petani yang mengalami kerugian akibat kerusakan tanaman yang disebabkan oleh faktor alam seperti kekeringan, banjir, dan serangan hama asuransi diberikan melalui, Program Asuransi Usaha Tani Padi (AUTP). Tujuan penelitian adalah untuk mengetahui respon petani yang membudidayakan tanaman padi terhadap AUTP di Desa Gondangmanis Kecamatan Bandarkedungmulyo Kabupaten Jombang. Pada penelitian ini, sampel petani yang dipakai menjadi objek penelitian melibatkan 118 petani penggarap yang pernah menerima program AUTP sebagai responden terhadap program AUTP. Jumlah responden adalah 6 yang mengikuti program AUTP pada kelompok tani Manisrenggo dan 6 responden mengikuti program AUTP pada kelompok tani, Gondangmanis. Terdapat dua data yang dijadikan sumber pada penelitian ini yaitu data primer dan data sekunder. Data penelitian dianalisis menggunakan uji validitas dan uji reliabilitas. Respon petani terhadap pelaksanaan program AUTP bernilai 69,92. Nilai ini memiliki rata-rata rumus indeks sebesar 87,40 % menunjukkan arti bahwa responden Sangat Setuju (ss) terhadap tujuan, manfaat dan pelaksanaan program AUTP di Desa Gondangmanis Kecamatan Bandarkedungmulyo Kabupaten Jombang.